2014
DOI: 10.1007/s10067-014-2719-7
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of methotrexate and celecoxib increases risk of silent liver fibrosis in rheumatoid arthritis patients with subclinical reduced kidney function

Abstract: We evaluated the effects of concurrent use of methotrexate and celecoxib on silent liver and kidney damages in rheumatoid arthritis (RA) patients. We enrolled 92 RA patients with normal laboratory results related to liver and kidney functions, who had received methotrexate and celecoxib concurrently over 6 months. Liver stiffness measurement (LSM) using transient elastography and ultrasonography were performed along with blood and urine tests. Estimated glomerular filtration rate (eGFR) was calculated by both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, several studies have demonstrated the adverse effects of MTX in long term or high dose treatment; one of the major concerns being its pro-oxidant and non-specific action [5]. The average MTX levels in cerebrospinal fluid and serum is reported to be 17.1 μM and 779 μM respectively in various cancer patients treated with high-dose MTX [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated the adverse effects of MTX in long term or high dose treatment; one of the major concerns being its pro-oxidant and non-specific action [5]. The average MTX levels in cerebrospinal fluid and serum is reported to be 17.1 μM and 779 μM respectively in various cancer patients treated with high-dose MTX [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to a lack of precise recommendations, most physicians only monitor the aminotransferase level in serum, which may but does not always correspond to the extent of liver damage. Liver fibrosis might progress silently without an apparent elevation of the aminotransferase serum level [ 11 , 12 , 15 , 16 ]. Liver biopsy, on the other hand, carries the risk of morbidity and even mortality, which highlights the need for new, less invasive methods.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, an interconnection between the cumulative dose of MTX and the TE result was not observed [3,10,12,[14][15][16][17][18][19][20]. Only two studies reported the opposite result [11,13].…”
Section: Mtx Might Accelerate the Process Of Fibrosis In Predisposedmentioning
confidence: 98%
“…They recommended TE as an added diagnostic option 7 . A second Korean study assessed celecoxib with MTX and postulated that low estimated glomerular filtration rate may predict the development of silent liver fibrosis 8 . They recommended TE to monitor for MTX toxicity in patients with chronic kidney disease with low estimated glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…7 A second Korean study assessed celecoxib with MTX and postulated that low estimated glomerular filtration rate may predict the development of silent liver fibrosis. 8 They recommended TE to monitor for MTX toxicity in patients with chronic kidney disease with low estimated glomerular filtration rate. A 2012 prospective Korean trial found leflunomide use was an independent predictor of abnormal LSM values in MTX-exposed individuals.…”
Section: Transient Elastographymentioning
confidence: 99%